Living lights of the night ecological landscape design of UP Diliman for Firefly Habitat Conservation - Puno, Alexis Anne U.
Often overlooked among the faunas present in the University of the Philippines Diliman campus are the insects. To add to this, many people are not aware of the huge contribution of insects to biodiversity, as they serve as pollinators, decomposers, soil aerators, pest controllers, and since they are located at the lower end of the food chain, they serve as food for various organisms, including birds. Therefore, in UP Diliman, where bird conservation is a primary advocacy, it is only fitting that a significant part of this advocacy be focused on insect conservation. And one of the ways to promote insect conservation is through a flagship species or a species which lives in a variety of habitats, considered to be charismatic, and could therefore represent a certain campaign. One such insect in the campus with the described traits is the firefly. They are adored by many for their light displays and they live in either wetlands, riparian areas, or terrestrial areas, and they are also sensitive to light pollution, which makes them a suitable icon in campaigns on insect conservation and campaigns against light pollution. In the Diliman campus, the fireflies face threats which include light pollution and habitat disturbances (habitat-destructive developments, mowing of grass, trampling, etc.) which contributes to the degradation of the firefly habitats. With that said, the main goal of this research is to address the degradation of the firefly habitats in the campus through ecological landscape design. Specific design solutions for the study include the formulation of planting designs and schemes, and habitat protection guidelines and policies, and the creation of a design template for new habitats and habitat connections to strengthen existing habitat patches. Through the realization of such measures, the study could eventually help other insect populations, promote and raise awareness on insect conservation.